2019
DOI: 10.22146/ijc.45777
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxicity Evaluation and Molecular Docking Studyof <i>N</i>-Phenylpyrazoline Derivatives

Abstract: The synthesis of N-phenylpyrazolines 1-5 was performed by the cyclocondensation of phenylhydrazine and appropriate chalcones that have been synthesized from our previous work. All of the compounds were elucidated for their structure using GC-MS, FTIR, 1H, and 13C-NMR spectrometers. Their anticancer activity was evaluated against breast cancer cell line (T47D) and colorectal cancer cell line (WiDr). Compound 4 (4-(3-(4-chlorophenyl)-1-phenyl-4,5-dihydro-1H-pyrazol-5-yl)-2-methoxyphenol) was found to be the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Docking result suggested that thioxanthones TX3 ‐ 6 were active against cancer cells that express EGFR protein. The cancer cells that express EGFR protein were in breast, [25] cervical, [26] lung, [27] and colorectal cancer [28] . Therefore, the synthesized thioxanthones TX3 ‐ 6 were evaluated through the MTT assay against breast (T47D), cervical (HeLa), colorectal (WiDr), and lung (A549) cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Docking result suggested that thioxanthones TX3 ‐ 6 were active against cancer cells that express EGFR protein. The cancer cells that express EGFR protein were in breast, [25] cervical, [26] lung, [27] and colorectal cancer [28] . Therefore, the synthesized thioxanthones TX3 ‐ 6 were evaluated through the MTT assay against breast (T47D), cervical (HeLa), colorectal (WiDr), and lung (A549) cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…[20,21] In many cases, PDGFR protein is often overexpressed in the lung, [18] breast, [22] glioma, [23] and ovarian [24] cancer cell lines. While EGFR protein is expressed in breast, [25] cervical, [26] lung, [27] and colorectal [28] cancer cells. In our previous work on the molecular docking study of thioxanthone derivatives, it was revealed that the important factors influencing their binding energy were the presence of hydroxyl and halogen (i. e., chloro (Cl) and bromo (Br)) substituents.…”
Section: Introductionmentioning
confidence: 99%
“…The last five years' studies found that the pyrazoline and N-phenyl pyrazoline derivatives targeted the EGFR. 12,13 The EGFR signaling pathway is a well-known signaling pathway that regulates cancer cell proliferation, tumor growth, and metastasis in cancers. Further, the human papillomavirus infection is well known as the main cause of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Indones J Chem. 2019;19(4):1081-1090. doi:10.22146/ijc.45777 Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License 12.…”
mentioning
confidence: 99%
“…Globally, cancer is one of the serious and dreadful diseases characterized by the uncontrolled, rapid, and pathological proliferation of cells (Chavan et al, 2018). In underdeveloped countries incidence and mortality rate due to cancer increases day to day because of the growth and aging of the population (Suma et al, 2019). As per a survey by GLOBO-CAN in 2018, over 18.1 million new cancer cases and 9.6 million deaths till now and the cases may gradually raise up to 23.6 million by 2030 (Suma et al, 2019;Santosh et al, 2019;Jemal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%